A study on the early streamer emission (ESE) lightning protection system [compact disc] - 446955 Ngu, Eng Eng (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2004